The embattled constitution - Dorsen, Norman; DeJulio, Catherine (New York : New York University Press, 2016)
This title presents the fourth collection of the James Madison lectures delivered at the NYU School of Law, offering thoughtful examinations of an array of topics on civil liberties by a distinguished group of federal judges, including Justice Stephen Breyer of the US Supreme Court. The result is a fascinating look into the minds of the judges who interpret, apply, and give meaning to the US Constitution.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: Constitutional law -- United States; Law; United States of America, USA; Constitution: government & the state; Jurisprudence & general issues; Laws of specific jurisdictions & specific areas of law; Constitutional & administrative law: general